Accurate and Robust Spectral Testing with Relaxed Instrumentation Requirements - Zhuang, Yuming; Chen, Degang; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book introduces a family of new methods for accurate and robust spectral testing and fills an information gap, as the requirements in standard test have grown increasingly challenging in recent high precision testing, especially as the device performance has continued to improve. Test engineers will be enabled to accurately set their devices & systems at much simpler test setup, much reduced complexity and much lower cost.
Chapter 1. Introduction -- Chapter 2.Algorithms for accurate spectral analysis in the presence of arbitrary non-coherency and large distortion -- Chapter 3.Accurate spectral testing with arbitrary non- coherency in sampling and simultaneous drifts in amplitude and frequency -- Chapter 4.High-purity sine wave generation using nonlinear DAC with pre-distortion based on low-cost accurate DAC-ADC co-testing -- Chapter 5.Low cost ultra-pure sine wave generation with self-calibration -- Chapter 6.Accurate spectral testing with non-coherent sampling for multi-tone test -- Chapter 7.Accurate spectral testing with impure test stimulus for multi-tone test -- Chapter 8.Multi-tone sine wave generation achieving the theoretical minimum of peak-to-average power ratio -- Chapter 9.Accurate linearity testing using low purity stimulus robust against flicker noise -- Chapter 10.Summary.
Keywords: Electronic circuits; Electronics; Electronic Circuits and Systems; Electronics and Microelectronics, Instrumentation